2008
DOI: 10.1016/j.jmps.2007.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance measurement of transient shear wave propagation in a viscoelastic gel cylinder

Abstract: A magnetic resonance measurement technique was developed to characterize the transient mechanical response of a gel cylinder subjected to angular acceleration. The technique employs tagged magnetic resonance imaging (MRI) synchronized to periodic impact excitation of a bulk specimen. The tagged MRI sequence provides, non-invasively, an array of distributed displacement and strain measurements with high spatial (here, 5 mm) and temporal (6 ms) resolution. The technique was validated on a cylindrical gelatin sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 18 publications
0
36
0
Order By: Relevance
“…This invariant measure combines both principal strain components. Previous studies using this device reported radial-circumferential shear strain values because this component dominates the deformation, and has a clear physical interpretation, including the meaning of positive and negative values (Bayly et al, 2008; Sabet et al, 2008). For comparison, images of the raw radial-circumferential strain values for all experiments from the human subjects are provided in Supplemental Figures 4–6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This invariant measure combines both principal strain components. Previous studies using this device reported radial-circumferential shear strain values because this component dominates the deformation, and has a clear physical interpretation, including the meaning of positive and negative values (Bayly et al, 2008; Sabet et al, 2008). For comparison, images of the raw radial-circumferential strain values for all experiments from the human subjects are provided in Supplemental Figures 4–6.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the experiment, the phantom was allowed to equilibrate to room temperature for at least 8 hours. The response of thegelatin cylinder to mild angular acceleration has previously been characterized using tagged MRI and compared to a numerical simulation (Bayly et al, 2008). Additionally, the gelatin phantom can be imaged for a longer period of time than human subjects.…”
Section: Methodsmentioning
confidence: 99%
“…13). Images of gel deformation were obtained using an analytical model and solution described in Bayly et al (2007). The gel is intended only as a qualitative analog to the brain, but the shear moduli are within the range of values reported for fresh mammalian brain (e.g., Thibault and Margulies, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…HARP has been validated in synthetic images [19] and in a gel phantom under shear [20]. Normal strain mean and SD by segment were determined from volunteer images.…”
Section: Methodsmentioning
confidence: 99%